Hildegard of Bingen’s symphony of deification and mystical union - Paniel Reyes Cárdenas (A&H)
In this article the topic of research will be Hildegard's engagement with the tradition of deification (divinisation), also known as the “mystical tradition”. After introducing the topic of deification, I delve into the luminous depths of Hildegard of Bingen's mystical vision, exploring her engagement with the profound tradition of deification, or theosis. This mystical tradition, woven through the tapestry of Christian thought, envisions the human journey as an ascent toward union and participation in the divine life. We will illuminate this theme through the prism of Hildegard's visionary writings, particularly focusing on several salient passages from her Scivias. I will particularly focus on some of her visions that are particularly salient in this regard: Book 1 v. 1 and Book 3 v. 1, 12 and 13. With some of the traits in these visions, I shall substantiate the claim that she rightly belongs to the tradition of mysticism of deification.